Integrating Maritime Law Education and Navigation Skills: Enhancing Vocational School Curriculum - Tri Cahyadi; Ahmad ahmad; Larsen Barasa (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
This research investigates the integration of maritime law education and navigation skill development within vocational school settings. By leveraging qualitative methods, the study engages maritime professionals and vocational educators to assess curriculum effectiveness and alignment with industry standards. Key findings highlight the importance of practical application in maritime law education, emphasizing case studies and scenario-based learning to prepare cadets for real-world challenges. Simulator training emerges as pivotal in developing navigation skills and critical decision-making abilities essential for safe maritime operations. The study also underscores the significance of regulatory compliance, advocating for continuous curriculum adaptation to meet evolving STCW and IMO regulations. Recommendations include enhancing collaboration between stakeholders, expanding experiential learning opportunities, and integrating regulatory awareness throughout educational frameworks. By fostering these initiatives, vocational schools can nurture competent maritime professionals equipped to navigate global maritime challenges while upholding safety, sustainability, and regulatory standards.